Rotating Machinery, Vibro-Acoustics & Laser Vibrometry, Volume 7 Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics 2018 - Di Maio, Dario; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Rotating Machinery, Vibro-Acoustics & Laser Vibrometry, Volume 7: Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics, 2018, the seveth volume of nine from the Conference brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Rotating Machinery, Hybrid Testing, Vibro-Acoustics & Laser Vibrometry, including papers on: Rotating Machinery Vibro-Acoustics Experimental Techniques Scanning Laser Doppler Vibrometry Methods.
Chapter 1. Summarizing Results for Scaling OMA Mode Shapes by the OMAH Technique.-  Chapter 2. Delamination Identification of Laminated Composite Plates Using a Continuously Scanning Laser Doppler Vibrometer System -- Chapter 3. Rapid and Dense 3D Vibration Measurement by Three Continuously Scanning Laser Doppler Vibrometers.-  Chapter 4. Modal Control of Magnetic Suspended Rotors -- Chapter 5. On the Implementation of Metastructures in Rotordynamics -- Chapter 6. Analysis of the Dynamic Response of Coupled Coaxial Rotors -- Chapter 7. Operational Modal Analysis of Rotating Machinery -- Chapter 8. Characterization of Torsional Vibrations: Torsional-Order Based Modal Analysis -- Chapter 9. Long-Term Automatic Tracking of the Modal Parameters of an Offshore Wind Turbine Drivetrain System in Standstill Condition -- Chapter 10. Dynamic Modelling and Vibration Control of a Turbomolecular Pump with Magnetic Bearings in the Presence of Blade Flexibility -- Chapter 11. Pushing 3D Scanning Laser Doppler Vibrometry to Capture Time Varying Dynamic Characteristics -- Chapter 12. Dynamic Measurements on Miniature Springs for Flaw and Damage Detection -- Chapter 13. Using High-Resolution Measurements to Update Finite Element Substructure Models -- Chapter 14. Determination of Representative Offshore Wind Turbine Locations for Fatigue Load Monitoring by Means of Hierarchical Clustering -- Chapter 15. Effect of Friction-Induced Nonlinearity on OMA-Identified Dynamic Characteristics of Offshore Platform Models -- Chapter 16. Remote Damage Detection of Rotating Machinery -- Chapter 17. Experimental Demonstration of a Tunable Acoustoelastic System -- Chapter 18. Numerical Modeling of an Enclosed Cylinder. - Chapter 19. Exploiting Laser Doppler Vibrometry in Large Displacement Tests -- Chapter 20. A Rational Basis for Determining Vibration Signature of Shaft/Coupling Misalignment in Rotating Machinery -- Chapter 21. Parametric Experimental Modal Analysis of a Modern Violin Based on a Guarneri del GesùModel -- Chapter 22. Influence of the Harmonics on the Modal Beahvior of Wind Turbine Drivetrains -- Chapter 23. The Influence of Geometrical Correlation in Modal Validation Using Automated 3D Metrology.
Keywords: Machinery; Multibody systems; Vibration; Mechanics, Applied; Acoustical engineering; Lasers; Machinery and Machine Elements; Multibody Systems and Mechanical Vibrations; Engineering Acoustics; Laser